Allergic thrombocytopenic purpura - Zegarra Puppi, José (1965)
In the broad field of Medical Pathology the purpuric syndromes linked to allergic phenomena have acquired special importance due to the progress of medicine in the field of immuno- hematology. These studies highlight the singular charge pathogenesis of immune thrombocytopenia . Until 15 years ago the theories explaining the purple thrombocytopenic mainly concerned that depressed splenic hyperfunction maturation of megakaryocytes or platelets or exit the spleen " kidnapped " the circulating blood platelets produce the corresponding deficit ( 1 ) . These theories that tried to explain certain thrombocytopenic purple did not meet the scientific requirements so that they can definitely accept as causal of thrombocytopenia . In 1951 Evans (2) and Harrington ( 3) show a large percentage of trombocipoténicas purple , agglutinins antiplaquctarias disappearing or decreased according to disease progression .